Paediatric ovarian torsion: a case report and review of literature - ., Umang; Cheema, Harleen Kaur; Khullar, Sidharth; Nagpal, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian torsion is a surgical emergency, can result in ovarian loss, intra-abdominal infection and even death. Paediatric ovarian torsion is a rare condition, requires high clinical suspicion and prompt diagnosis. Diagnosis is a challenge since signs and symptoms are similar to those of other causes of acute abdominal pain such as appendicitis, gastroenteritis, urinary tract infection, renal colic or other conditions of acute abdominal and pelvic pain. Here, authors describe a case of a 4-year-old girl with a presentation of acute abdominal pain, treated empirically elsewhere. After investigations, a provisional diagnosis of ovarian torsion was made and patient was taken up for surgery. Intraoperatively, ovary was found to be necrosed. Detorsion was tried but ovary was unsalvageable. Right sided salpingectomy with oophorectomy was performed. Conservative surgery by laparoscopic detorsion can be tried in cases of ischemia but if necrosis has already set in, then salpingo-oophorectomy has to be performed.